Factors related to preventive behaviors among parent caregivers of children under five years with acute respiratory tract infection in Myanmar - Thaw, Sandi; Santati, Sermsri; Pookboonmee, Renu (Makara Journal of Health Research, 2019)
Background: Acute respiratory tract infection (ARI) is the second-leading cause of death worldwide among children, especially among those aged <5 years. Thus, it is imperative to understand parent caregivers’ perception of ARI and their preventive behaviors. Methods: This descriptive correlation study included 116 parent caregivers at an out-patient department of a 550-bedded Children Hospital, in Mandalay, Myanmar. The correlation between preventive behaviors and parent caregivers’ perception on ARI was measured using Becker’s Health Belief Model-based questionnaires. Descriptive statistics and spearmen’s rank-order collection test were used for data analysis. Results: Our results revealed that parent caregivers’ perception was at a moderate level, and preventive behaviors among parent caregivers were at a poor level during wellness and sickness conditions. The average score of the parent caregivers’ preventive behaviors in ARI was 23.57 ± 3.22). Significant positive relationships were noted between perceived susceptibility, perceived severity, perceived benefits, and cues to action and preventive behaviors of parent caregivers (p < 0.05, p < 0.01, p < 0.05, and p < 0.01, respectively). Conclusion: The results supported the health belief model: Health care personnel should provide a theory-based health education program toward improving the parent caregivers’ preventive behaviors with ARI children.